Radiographic changes of the mid-tarsal joint after calcaneal lengthening for planovalgus foot deformity - Sung, Ki Hyuk; Kwon, Soon Sun; Chung, Chin Youb; Lee, Kyoung Min; Park, Moon Seok (Foot and Ankle Surgery, 2020)
Background: This study evaluate the radiographic changes in the mid-tarsal joint, including the calcaneocuboid and talonavicular (TN) joints after calcaneal lengthening for planovalgus deformity in children. Methods: This study included 38 patients (68 feet) who underwent calcaneal lengthening for planovalgus deformity. Radiographic osteoarthritic changes at the CC or TN joint were defined as modified Kellgren–Lawrence grade of ≥1. Results: Among the 68 feet, 31 feet (45.6%) showed radiographic osteoarthritic changes at the CC joint and 20 (29.4%) showed changes at the TN joint. Risk of radiographic osteoarthritic changes at the CC joint was associated with increased age at surgery (OR = 1.2, p = 0.038). Risk of radiographic osteoarthritic changes at the TN joint was associated with increased age at surgery (OR = 2.2; p = 0.002), preoperative AP talus-1st metatarsal angle (OR = 1.1; p = 0.044), and degree of CC subluxation (OR = 2.1; p = 0.007). Conclusions: Surgeons should consider the risk factors in the surgical correction of planovalgus deformity to prevent mid-tarsal arthritis.
Keywords: Adolescent; Calcaneus; Child; Child, Preschool; Female; Foot Deformities; Humans; Radiography; Retrospective Studies; Risk Factors; Tarsal Joints; Young Adult; Calcaneal lengthening; Mid-tarsal joint; Planovalgus deformity; Radiographic osteoarthritic change